Beginning Google Maps Applications with Rails and Ajax From Novice to Professional - Lewis, Andre; Turner, Cameron; Sambells, Jeffrey; Purvis, Michael (Apress : Imprint: Apress, 2007)
The Google Maps API remains one of the showcase examples of the Web 2.0 development paradigm. Beginning Google Maps Applications with Rails and Ajax: From Novice to Professional is the first book to comprehensively introduce the service from a developer perspective, showing you how you can integrate mapping features into your Rails-driven web applications. Proceeding far beyond simplistic map display, youll learn how to draw from a variety of data sources such as the U.S. Census Bureau's TIGER/Line data and Google's own geocoding feature to build comprehensive geocoding services for mapping many locations around the world. The book also steers you through various examples that show how to encourage user interaction such as through pinpointing map locations, adding comments, and building community-driven maps. Youll want to pick up a copy of this book because This is the first book to comprehensively introduce the Google Maps application development using the Rails development framework. Youll be introduced to the very latest changes to the Google Maps API, embodied in the version 2 release. It is written by four developers actively involved in the creation of location-based mapping services. For additional info, please visit the author's reference site for this book.